Evaluation Of Park Facility Provisions By Residents Of Seri Manjung New Town, Perak Darul Ridzuan - Wan Omar, Wan Rabiah (2004)

(untitled)
This study was undertaken to evaluate the extent of existing residential park facilities provision in Seri Manjung New Town, Perak Darul Ridzuan in fulfilling users’ recreation needs. Basically, this study answered four objectives namely, to compare the provision of existing park facilities with the Planning Standard requirement, to describe current use pattern of residential parks in Seri Manjung New Town, and to estimate users’ recreation needs based on the Importance Performance Analysis of residential park facilities. The data was successfully collected through park observations and questionnaire survey. The response rate for questionnaire survey was good whereby all 420 questionnaires from sample respondents were successfully collected. Descriptive analysis and Importance Performance Analysis (IPA) were applied as the main instruments to evaluate park facility performance. The use pattern of residential parks in the study area was described based on nine items namely income, frequency of park visit, age group, gender, visiting time, guardian permission, night park visit, popular recreation activity, and responsibility towards park facility. The IPA assessed the park facilities performance in fulfilling users’ needs. The outcomes of this study generally showed that Manjung Municipal Council failed to meet the standard requirement in the provision of park facilities in the study area. Among the seven parks, only one park achieved 67% compliance rate, four (4) parks at 50% and two (2) parks managed to comply only 25% of the standard requirement. Findings on the IPA indicated that among the seven residential parks, three parks needed attention (high importance but low performance) while the rest were rated as good work (high importance and high performance).